2017
DOI: 10.1016/j.rasd.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ perceptions of dental care challenges in male children with autism spectrum disorder: An initial qualitative exploration

Abstract: Background Many children with autism spectrum disorders (ASD) experience barriers to oral care in the dental office setting. The purpose of this study was to provide an increased understanding of these challenges experienced during oral care in the dental office by children with ASD. Method This study was part of a larger mixed methods design and builds on quantitative results from a survey of parents of children with ASD ages 2–18 in which parents reported difficulties with access to care, sensory processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 27 publications
(40 reference statements)
3
55
0
3
Order By: Relevance
“…It is important to note that health care experiences of all individuals may differ greatly from country to country. In addition, there is a growing body of literature examining families' perspectives of health care specialties, which were not included in the present review, such as anaesthesia (e.g., Arnold et al, 2015) and dental care (e.g., Duker et al, 2017) for children with ASD. Some studies identified similar challenges as those outlined in this review, such as difficulty with finding a suitable dentist and sensory sensitivities (Duker et al, 2017).…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that health care experiences of all individuals may differ greatly from country to country. In addition, there is a growing body of literature examining families' perspectives of health care specialties, which were not included in the present review, such as anaesthesia (e.g., Arnold et al, 2015) and dental care (e.g., Duker et al, 2017) for children with ASD. Some studies identified similar challenges as those outlined in this review, such as difficulty with finding a suitable dentist and sensory sensitivities (Duker et al, 2017).…”
Section: Limitationsmentioning
confidence: 99%
“…In addition, there is a growing body of literature examining families' perspectives of health care specialties, which were not included in the present review, such as anaesthesia (e.g., Arnold et al, 2015) and dental care (e.g., Duker et al, 2017) for children with ASD. Some studies identified similar challenges as those outlined in this review, such as difficulty with finding a suitable dentist and sensory sensitivities (Duker et al, 2017). Other studies have found very few differences between the experiences of children with ASD and other children (Arnold et al, 2015).…”
Section: Limitationsmentioning
confidence: 99%
“…While visits to the dentist can provoke anxiety in many (with around 36% of adults having some form of dental anxiety), 8 the increased susceptibility to clinical levels of anxiety can make dental visits particularly distressing for autistic individuals. 9,10,11,12 In line with all these challenges discussed above, several studies (conducted in the US and Saudi Arabia) regarding the dental experiences of autistic people have reported significant difficulties in accessing adequate dental care. 2,13,14,15 This has wide-ranging consequences: poor oral healthcare can lead to pain, eating difficulties and speech impairments among other ailments.…”
Section: Introductionmentioning
confidence: 88%
“…Se trata de una alteración del desarrollo neurológico caracterizada por "problemas en la interacción social, dificultad de comunicación y conductas repetitivas y limitadas". Conforme ha pasado el tiempo, la incidencia del autismo se ha incrementado sustancialmente [129,130]. Así, en un estudio realizado en 2012 por el [141].…”
Section: 83unclassified
“…la incidencia actual de trastornos del espectro autista ronda el 0.69% o 1/145 niños". En España, los últimos datos sobre personas diagnosticadas con algún tipo de trastorno del espectro autista informan sobre unas 25.000 personas en 2005.Posteriormente, en la Encuesta de Discapacidad, Autonomía Personal y Situaciones de Dependencia realizada por el INE en el año 2008 se habla de valores de 13.800 Heridas auto-infligidas en pacientes con autismo.En estos pacientes se ha observado en la mayoría de artículos que hay una peor salud oral, en términos de prevalencia y severidad de caries y de enfermedad periodontal, afectando negativamente a la salud y la calidad de vida[8,130].Así, Önol y cols. (2018)[129] comparan los índices de placa y gingival de pacientes autistas con niños sin autismo, siendo mayores en el primer grupo de forma significativa.…”
unclassified